Primary cilium-mediated MSC mechanotransduction is dependent on Gpr161 regulation of hedgehog signalling. - Hoey, David (My University, 2021)
The benefits of physical loading to skeletal mass are well known. The primary cilium has emerged as an important organelle in bone mechanobiology/mechanotransduction, particularly in mesenchymal stem/stromal cells, yet the molecular mechanisms of cilium mechanotransduction are poorly understood. In this study, we demonstrate that Gpr161 is a mechanoresponsive GPCR, that localises to the cilium, and is involved in fluid shear-induced cAMP signalling and downstream osteogenesis. This Gpr161-mediated mechanotransduction is dependent on IFT88/cilium and may act through adenylyl cyclase 6 (AC6) to regulate cAMP and MSC osteogenesis. Moreover, we demonstrate that Hh signalling is positively associated with osteogenesis and that Hh gene expression is mechanically regulated and required for loading-induced osteogenic differentiation through a mechanism that involves IFT88, Gpr161, AC6, and cAMP. Therefore, we have delineated a molecular mechanism of MSC mechanotransduction which likely occurs at the cilium, leading to MSC osteogenesis, highlighting novel mechanotherapeutic targets to enhance osteogenesis.
PUBLISHED
Keywords: Bone; Osteogenesis; G protein coupled receptor; Mesenchymal Stem/Stromal Cell; Oscillatory fluid shear